2010
DOI: 10.1163/22941932-90000016
|View full text |Cite
|
Sign up to set email alerts
|

Wood Anatomy of nine Japanese Hardwood species forming reaction wood without gelatinous fibers

Abstract: The anatomy of reaction wood was studied in nine naturally growing Japanese hardwood species, all showing eccentric growth on the upper side of their leaning branches. The number of vessels decreased in the xylem of the upper side accompanying the formation of reaction wood. A typical G-layer was not detected in the reaction wood fibers, but an S3 layer was present in all nine species. The cellulose microfibril arrangement with an S helix was similar in the S3 layers of both reaction and opposite wood fibers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Although the GL is the most important structural change of tension wood in most temperate eudicots, numerous tropical species do not produce a GL (Okuyama et al 1994;Yoshida et al 2000;Clair et al 2006, Sultana et al 2010. In tension wood with G-fibres, the GL is recognized as the driving force of tensile stress as its amount is directly related to the mechanical stress level (Clair et al 2003, Washusen et al 2003, Fang et al 2008 and tensile stress in cellulose microfibrils has been identified to occur synchronously with their deposition in the GL during cell maturation (Clair et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the GL is the most important structural change of tension wood in most temperate eudicots, numerous tropical species do not produce a GL (Okuyama et al 1994;Yoshida et al 2000;Clair et al 2006, Sultana et al 2010. In tension wood with G-fibres, the GL is recognized as the driving force of tensile stress as its amount is directly related to the mechanical stress level (Clair et al 2003, Washusen et al 2003, Fang et al 2008 and tensile stress in cellulose microfibrils has been identified to occur synchronously with their deposition in the GL during cell maturation (Clair et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, S 1 layer is formed first and following S 2 and S 3 layers are deposited in the inner side of fiber cell lumen. Recently, we [23] reported this structure in reaction wood fiber without a G-layer for the first time (Fig. 2, Fig.…”
Section: Middle Lamellamentioning
confidence: 71%
“…Tension wood is an abnormal wood formed typically on the upper side of branches and leaning or crooked stems of dicotyledonous trees. Tension wood differs from normal wood with the following main characteristics: i) Radial growth increment at upper side of leaning stem or branch is found in stem cross section [6,18,22,23], ii) Green-sawn boards of tension wood are woolly surface [6], iii) Wider rings are found in tension wood zone [24], iv) The size and number of vessels decrease with the formation of tension wood in generally [5,25,26], v) An internal gelatinous layer (G-layer) is present in tension wood fibers [5,21,27], which contains extensive α-cellulose, is unlignified or less lignified and microfibrils in G-layer are oriented nearly parallel or parallel along the axis of the fiber [28,29], vi) Particularly, tensile strength in tension wood is high, is found on upper side at either presence of G-layer [22,30] or absence of G-layer [31] in tension fiber, vii) The microfibril angles in S 2 layer of tension wood fiber are smaller than that of normal wood [25] and they are oriented nearly parallel or parallel in G-layer of the fiber [28,29], and viii) Lignification of tension wood is lesser that normal wood [6,[32][33][34][35]].…”
Section: Tension Wood Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was reported that tensile growth stress significantly increased in reaction wood of two Magnolia species, resulting in decrease of the microfibril angle of S2 layer and increase of the α-cellulose content [15]. Sultana et al [51] reported that only two species showed the smaller microfibril angles in the S2 layers of reaction wood fibers compared to the opposite wood fibers. However, no significant, but relatively high negative correlation was found between decrease rate of microfibril angle and growth eccentricity rate.…”
Section: Microfibril Angle In Tension Wood Fibermentioning
confidence: 99%